Endgame : : the calling - Frey, James,, 1969-; Johnson-Shelton, Nils. (New York :: HarperCollins, an imprint of HarperCollinsPublishers, 2014)
Summary
Keywords: Science fiction; Survival; Contest; JUVENILE FICTION / Action & Adventure / Survival Stories; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Science Fiction